Peptide Profile of Zebrafish Brain in a 6-OHDA-Induced Parkinson Model - Fiametti, Louise Oliveira [UNESP]; Correa, Claudia Neves [UNESP]; Castro, Leandro Mantovani De [UNESP] (SAGE Publications, 2021)
Parkinson's disease (PD) is a chronic neurodegenerative disorder mainly attributed to the progressive loss of dopaminergic neurons in the substantia nigra, which leads to uncontrolled voluntary movements causing tremors, postural instability, joint stiffness, and speech and locomotion difficulties, among other symptoms. Previous studies have shown the participation of specific peptides in neurodegenerative diseases. In this context, the present work analyzed changes in the peptide profile in zebrafish brain induced to parkinsonian conditions with 6-hydroxydopamine, using isotopic labeling techniques plus mass spectrometry. These analyses allowed the relative quantitation and identification of 118 peptides. Of these, nine peptides showed significant changes, one peptide was increased and eight decreased. The most altered sequences were fragment of cytosolic and extracellular proteins related to lipid metabolism and dynamic cytoskeleton. These results open new perspectives of study about the function of peptides in PD.
Keywords: mass spectrometry; neurodegenerative disease; peptidomics; zebrafish